2013
DOI: 10.1016/j.procbio.2013.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the immobilization of sweet potato amylase using glutaraldehyde-agarose support. Characterization of the immobilized enzyme

Abstract: A simplified procedure for the preparation of immobilized beta-amylase using non-purified extract from fresh sweet potato tubers is established in this paper, using differently activated agarose supports. Beta-amylase glutaraldehyde derivative was the preparation with best features, presenting improved temperature and pH stability and activity. The possibility of reusing the amylase was also shown, when this immobilized enzyme was fully active for five cycles of use. However, immobilization decreased enzyme ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 35 publications
3
26
0
Order By: Relevance
“…The slower hydrolysis rate using immobilized trypsin was expected, and appears to be more related to diffusional problems of substrates, as described previously, than environmental conditions. As it is known, K m value can increase due to restricted diffusion of substrate or the high structural rigidity of immobilized enzyme (RODRIGUES et al, 2013;TAVANO et al, 2013). HOMAEI and co-workers (2010) observed a slight increase in K m value when papain was immobilized in cyanogen bromide activated Sepharose.…”
Section: Resultsmentioning
confidence: 99%
“…The slower hydrolysis rate using immobilized trypsin was expected, and appears to be more related to diffusional problems of substrates, as described previously, than environmental conditions. As it is known, K m value can increase due to restricted diffusion of substrate or the high structural rigidity of immobilized enzyme (RODRIGUES et al, 2013;TAVANO et al, 2013). HOMAEI and co-workers (2010) observed a slight increase in K m value when papain was immobilized in cyanogen bromide activated Sepharose.…”
Section: Resultsmentioning
confidence: 99%
“…Vretblad and Axen [66] reported a global yield of 35% for barley β-amylase covalently attached on Sepharose activated with 4,4 -methylene dianiline. Tavano et al [69] reported global yield of 21% for sweet potato β-amylase immobilized on glyoxyl-agarose support. These results are much closer to those obtained in our work for barley β-amylase ionically adsorbed on chitosan (Table 1).…”
Section: Optimization Of β-Amylase Immobilization Using Cleas Technologymentioning
confidence: 99%
“…The study of the effect of the reaction pH and temperature on the enzyme activity of β-amylase was performed using free enzyme, CLEA-β-BSA-5 and CLEA-β-SPI-12 to investigate the influence of the enzyme immobilization technique on enzyme response to the medium [68][69][70][71] (Figure 2). …”
Section: Effects Of Ph and Temperature On The Activity And The Stabilmentioning
confidence: 99%
See 1 more Smart Citation
“…The encapsulation efficiency is enhanced on the further addition of 2% (w/v) silica gel. Glyoxyl and glutatraldehyde supports can also be used for the stabilization of the enzyme by multipoint attachment (Tavano et al, 2013). Thus the most important aspect that has to be considered when immobilizing the amylase is the huge size of the substrate that cannot penetrate through the pores of the gel resulting in an inadequate accessibility of the enzyme to the substrate.…”
Section: Biofilm Removal Efficacymentioning
confidence: 99%